Nature and context of children's representations: Understanding of science concepts in drawings and drawing-making - Hernandez, Kristine Umali (Animo Repository, 2014)
Mark-making, storytelling, and play are all natural in children. They are as well inherent in children’s drawings. When children’s drawings tell us about children, their interests, their questions, and their thinking, drawing and drawing-making become empowering for children and their learning. It is in these perspectives that this research is initiated. Five case studies were conducted, within a span of four months, to examine the results of the drawing sessions when drawings were used to represent the understanding of a science concept in the different phases of its teaching in the classroom of each selected cases. Utilizing drawing samples, interview responses, and observation notes about the science teaching, children’s representations were analyzed and their representational context i.e. home and school were investigated to establish a framework for the use of drawings as an effective tool for learning and teaching of science concepts. Four themes have emerged in light of children’s representations about their understanding of science concepts. The theme on ‘power’ transpired in the analysis of the attitudes and intentions of children as drawing-makers. The theme about ‘control’ has surfaced when the style of children’s drawing-making was looked at. The theme about ‘voice’ became evident upon examination of the content and function of children’s drawings. The theme about ‘structure’ was apparent when views and practices about drawings and drawing-making were explored in the children’s representational learning environment.